Tools of the trade: click-tracks and conductors - Moore, Thomas R. (Interdisciplinary Studies in Musicology, 2020)
This essay will examine the manner in which composers and artistic directors have used conductors and click-tracks within the context of new music ensembles performing integrative concerts. The analyses and examples provided will rely for the most part on material gathered during in-depth interviews that I conducted with artistic directors, composers, conductors, and musicians, all of whom are professionally active in the new music field in Europe (and beyond). I will examine the application of both click-tracks and conductors and demonstrate that their implementation represents an active choice made by either the composer and/or artistic directors. Both click-tracks and conductors are viewed by the interviewees as potential tools with somewhat overlapping possibilities and capacities and their presence is no secondary phenomenon of the music. They become instead a means for the above actors to meet their objectives, be they artistic, pragmatic, technical, or otherwise.